Determinants of epilepsy among outpatients in public health institutions of Dawo district, South West Shoa Zone, Oromia, Ethiopia, 2023: an institutional-based unmatched case-control study - Alemu, Teshoma; Cheru, Abera; Daba, Lema; Tiki, Takele; Ifa, Meseret (Frontiers in Neurology, 2025)
BackgroundGlobally, in ~50% of epilepsy cases, the underlying cause remains unknown, despite the fact that various disease pathways may contribute to the condition. Nearly 80% of people with epilepsy live in low- and middle-income countries and the risk of premature death in people with epilepsy is up to three times higher than that for the general population. Identifying the determinants of epilepsy is important for applying evidence-based interventions to achieve a better outcome. However, this information is scarce in a country with limited resources like Ethiopia.ObjectiveThis study aimed to assess the determinant of epilepsy among outpatients in Dawo public health institutions, from 29 February to 15 April 2023.MethodAn institution-based unmatched case-control study design was used, involving 61 cases and 122 control study subjects, who were selected using a consecutive sampling technique from public health institutions in Dawo. Data were collected using a pre-tested structured questionnaire. The data were coded, entered into EpiDATA version 3.1, and exported to SPSS version 20, for further analysis. Descriptive analysis was used to determine the percentages and frequency distributions. Logistic regression analysis was used to identify the determinants of epilepsy, and a variable with p < 0.05 was considered statistically significant.ResultsA total of 61 cases and 120 controls were included in the study, with an overall response rate of 98.90%. The majority of participants, 38 (62.3) of the cases and 63 (52.5) of the controls, were farmers by occupation. A family history of epilepsy (AOR = 13.71 95% CI 3.030–22.006), history of febrile seizure (AOR = 14.57 95% CI 2.930–24.522), history of head injury (AOR = 6.853 95% CI 1.780–16.402), and non-use of latrine were found to be determinants of epilepsy (AOR = 0.028 95% CI 0.008–0.040).Conclusion and recommendationsThe current study identified a family history of epilepsy, a history of febrile seizures, head injury, and unavailability of latrines as independent predictors of epilepsy in the study area. The information that adverse febrile seizures increase the risk of epilepsy suggests that a significant proportion of epilepsy cases in Dawo district could be prevented through improved maternal, neonatal, and child care. It is recommended that the Dawo Health Office, along with relevant stakeholders, focus on addressing this issue at various levels.